Thinning Strategies to Optimize Genetic Gain and Population Size in Eucalyptus pellita Breeding - da Silva, Paulo Henrique Müller; Rocha, Guilherme Nichele da; Araujo, Marcio; Pires Nunes, Andrei Caíque; de Paula, Rinaldo Cesar [UNESP] (Springer Nature, 2024)
The study highlights the adaptability and potential of Eucalyptus pellita for forestry applications in Brazil. It utilized a randomized block design with linear plots of five plants across five replications, establishing an experimental trial with 175 progenies from several provenances in May 2019. The trial was conducted in Lençóis Paulista, São Paulo State, Brazil, which has an Aw (tropical wet-dry climate) climate according to Köppen´s classification and followed the commercial forestry practices of the region. Three years after planting, survival, height (H) and diameter at breast height (DBH) were measured, with the main annual increment calculated using a shape factor of 0.5. The survival rate reached 95%, with an average tree height of 12.6 m, DBH of 10 cm, and a volume mean annual increment of 34 m3ha− 1y− 1. We observed a provenance effect, with higher breeding values in improved material compared to wild (unimproved) material. Thinning strategies were initiated by plotting additive genetic effects for the DBH trait of families and provenance, resulting in the identification of four groups empirically divided according to the curve’s inflection point. Thinning intensity of 70 to 80% of the trees was found effective in maintaining both genetic gain and a good effective population size, regardless of whether selection within families was considered. Overall, the study emphasizes the importance of considering several factors, including provenance effects and selection strategies, for sustainable forestry practices. Provenance effects play a significant role in tree breeding programs. However, even within poor-performing provenance, it is possible to select trees with high breeding values.
Keywords: Forest genetic improvement; Genetic variability; Recurrent selections cycles; Red mahogany; Selection strategies